Effect of exercise training on nitric oxide and nitrate/nitrite (NOx) production: A systematic review and meta-analysis - Arefirad, Tahereh; Seif, Ehsan; Sepidarkish, Mahdi; Mohammadian Khonsari, Nami; Mousavifar, Seyedeh Azam; Yazdani, Shahrooz; Rahimi, Fatemeh; Einollahi, Faezeh; Heshmati, Javad; Qorbani, Mostafa (Frontiers in Physiology, 2022)
Background: Exercise and physical activity can improve circulation through various mechanisms, such as the increment of nitric oxide (NO) production, by affecting vascular endothelial nitric oxide synthase, and reducing reactive oxygen species (ROS). Although, theoretically, this mechanism is well known, studies in living subjects have made controversial findings regarding the association of NO production and its metabolites [nitrate/nitrite (NOx)] with physical activity. Hence, this systematic review and meta-analysis was designed to gather all these studies and evaluate the effects of exercise training, and physical activity duration and length on the mean change of serum/plasma NO and NOx. Method: We searched all available bibliographic electronic databases from inception through to May 2022 to include all randomized controlled trials (RCT) and quasi-experimental trials which assessed the effect of exercise and training on NO and NOx levels. Random-effects meta-analysis was used to pool the standardized mean difference (SMD) and 95% confidence interval (CI) of included RCT studies which assessed the effect of training. Stratified meta-analysis was performed according to the type of exercise (high-intensity interval training (HIIT), aerobic training (AT), the duration of exercise (≤8 and > 8 weeks), and length of exercise in each session ≥40 and 40 < minutes). Results: Overall, 15 and 10 studies were included in the systematic review and meta-analysis, respectively. According to the random-effects meta-analysis, exercise significantly increased the mean change of NO and NOx compared to control (SMD: 1.82, 95%CI: 1.14 to 2.49. In the stratified meta-analysis, the mean change of NO and NOx in the intervention group was significantly higher than in the control group in the AT (SMD: 1.36, 95%CI: 0.55–2.18), HIIT (SMD: 2.55, 95%CI: 1.14–3.96), duration of ≤8 (SMD: 2.29, 95%CI: 1.24–3.35) and > 8 weeks (SMD: 1.19, 95%CI: 0.52–1.86), length of ≥40 (SMD: 1.61, 95%CI: 1.04–2.18), and 40 < minutes in each session (SMD: 2.07, 95%CI: 0.79–3.35). Conclusion: The findings of this study indicate that, regardless of exercise duration, length, and type (AT or HIIT), exercise can significantly increase serum NO and NOx levels.